Rapid implementation and improvement of a virtual student placement model in response to the COVID-19 pandemic. Issue 4 (4th November 2020) - Twogood, Rory; Hares, Elly; Wyatt, Matthew; Cuff, Andrew
Abstract : Practice-based learning via clinical placement is a core part of a physiotherapy degree with the Chartered Society of Physiotherapy requiring completion of 1000 placement hours over a preregistration degree programme. In April 2020, as a result of the COVID-19 pandemic and subsequent lockdown Connect Health had to cancel 10 student placements as we transitioned to virtual consultations for all clinics. This cancellation of student placements was replicated across the nation with many Higher Education Institutes reporting a backlog of student placements. Without the requisite placement hours students are unable to progress into the next academic year or are unable to graduate. This then reduces the flow of new-graduate physiotherapists into the workforce at a time when there is a plan to grow the physiotherapy workforce to meet primary care demand. In response to this problem a novel placement model to facilitate virtual student placements ('virtual placements') was developed, tested and then rolled out across Connect Health using the Plan-Do-Study-Act quality improvement methodology. The model combines shadowing a broad range of virtual clinics with delivery of patient-facing online exercise classes via the Facebook Live platform and completion of virtual projects to support knowledge consolidation. This virtual student placement model enabled an increase in student capacity of over 400% compared with 2018–2019 with 182 students starting between May and August 2020. The model runs using widely available technology, requires no additional investment and has enabled these students to continue their studies and progress towards qualifying as physiotherapists.